HPAI drives a fourfold increase in adult gannet mortality which requires two decades recovery time - Jude V. Lane; Jason Matthiopoulos; David Astins; Ian Cleasby; Keith C. Hamer; Kirsty A. Franklin; Ruth Jeavons; Liam P. Langley; Aly McCluskie; Greg Morgan; Lisa Morgan; Christopher J. Pollock; et al. (Biological Conservation, 2026)

Hydrogen sulfide consumption by lunar regolith simulants - Cecilia L. Amick; Saunab Ghosh; Crystal A. Mantilla; Ernest K. Lewis; Christopher L. Harris; Ardith D. Bravenec; Michael C. Huh; Francis M. McCubbin; Jeremy W. Boyce (Icarus, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

State of deep-sea science and conservation in the Northeast Pacific: implications for policy and management - Fanny Girard; Joan M. Alfaro-Lucas; Amy R. Baco; James P. Barry; Katharine T. Bigham; Lara M. Beckmann; Angelika Brandt; Lindsay Clark; Megan A. Davies; Jeffrey C. Drazen; Anya Dunham; Cherisse Du Preez; et al. (Progress in Oceanography, 2026)

Carbon capture from ArcelorMittal hot briquetted Iron plant using air liquide cryocap™ FG technology – FEED study - Sebastiano Giardinella; Varun Gopalakrishnan; Vincent Gueret; Lindsey Turney; Vincent Lu; Chris Tovee; David Zybko; Marcelo Andrade; Christopher Harris; Pierre-Philippe Guerif; Timothy Henderson; Anderson Morelato; et al. (International Journal of Greenhouse Gas Control, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Bioenergy pathways within United States net-zero CO2 emissions scenarios in the Energy Modeling Forum 37 study - Ronald D. Sands; Liz Wachs; Patrick Lamers; Olivier Bahn; Robert H. Beach; Matthew Binsted; Geoffrey Blanford; Yongxia Cai; Francisco De La Chesnaye; James A. Edmonds; Leonard Göke; Chioke Harris; et al. (Energy and Climate Change, 2025)

Policy implications of net-zero emissions: A multi-model analysis of United States emissions and energy system impacts - John E.T. Bistline; Matthew Binsted; Geoffrey Blanford; Gale Boyd; Morgan Browning; Yongxia Cai; Jae Edmonds; Allen A. Fawcett; Jay Fuhrman; Ruying Gao; Chioke Harris; Christopher Hoehne; et al. (Energy and Climate Change, 2025)

Phytoplankton abundance and methane emissions are minimally impacted by environmentally-relevant glyphosate concentrations in small-scale outdoor mesocosms - Christopher F. Frazier; Ted D. Harris; Tonya DelSontro; Hans-Peter Grossart; Belinda S.M. Sturm; Jalynn M. Murry; Andrew Ising (Water Research, 2025)

The senescence-inhibitory p53 isoform Δ133p53α: enhancing cancer immunotherapy and exploring novel therapeutic approaches for senescence-associated diseases - Shinji Nakamichi; Leo Yamada; Christopher Roselle; Izumi Horikawa; Carl H. June; Curtis C. Harris (GeroScience, 2025)

Setting the limit: cold rather than hot temperatures limit intertidal distribution of a coastal foundation species - Kerstin Wasson; Kim Cressman; Kathryn Beheshti; Erin C. Herder; Charlie Endris; Christopher D.G. Harley; Alicia Abadía-Cardoso; Rodrigo Beas-Luna; Joachim Carolsfeld; Andrew L. Chang; Jeffrey A. Crooks; Matthew C. Ferner; et al. (Marine Environmental Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Pan-Canadian Predictive Modeling of Lithium–Cesium–Tantalum Pegmatites with Deep Learning and Natural Language Processing - Mohammad Parsa; Christopher J. M. Lawley; Tarryn Cawood; Tania Martins; Renato Cumani; Steven E. Zhang; Aaron Thompson; Ernst Schetselaar; Steve Beyer; David R. Lentz; Jeff Harris; Hossein Jodeiri Akbari Fam; et al. (Natural Resources Research, 2025)
The discovery of new lithium resources is essential because lithium plays a vital role in the manufacturing of green technology. Along with brines and volcano–sedimentary deposits, approximately a one-third share of global lithium resources is associated with lithium-cesium-tantalum (LCT) pegmatites, with Canada hosting numerous examples. This research applied generative adversarial networks, natural language processing, and convolutional neural networks to generate mineral prospectivity models and support exploration targeting for Canadian LCT pegmatites. Geoscientific text data included within public bedrock geology maps and natural language processing were used to convert conceptual targeting criteria into evidence layers that complement more traditional, geophysical and geochronological data used for mineral prospectivity modeling (MPM). A multilayer architecture of convolutional neural networks, including an attention mechanism, was designed for data modeling. This architecture was trained and validated using variable synthetically generated class labels, input image sizes, and hyperparameters, resulting in an ensemble of 1000 models. The uncertainty of the ensemble was analyzed using a risk–return analysis, yielding a bivariate choropleth risk–return plot that facilitates the interpretation of prospectivity models for downstream applications. This was further complemented by employing post hoc interpretability algorithms to translate the black-box nature of neural networks into comprehensible content. The low-risk and high return class of our prospectivity models reduces the search space for discovering LCT pegmatites by 88%, delineating 99% of known LCT pegmatites in Canada. The results of this study suggest that our workflow (i.e., combining synthetic data generation, natural language processing, convolutional neural networks, and uncertainty propagation for MPM) facilitates decision-making for regional-scale lithium exploration and could also be applied to other mineral systems.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

A systematic model- and experimental approach to hydro-mechanical and thermo-mechanical fracture processes in crystalline rocks - Olaf Kolditz; Christopher McDermott; Jeoung Seok Yoon; Mostafa Mollaali; Wenqing Wang; Mengsu Hu; Tsubasa Sasaki; Jonny Rutqvist; Jens Birkholzer; Jung-Wook Park; Chan-Hee Park; Hejuan Liu; et al. (Geomechanics for Energy and the Environment, 2025)

The Contemporary Distribution of Scincine Lizards Does Not Reflect Their Biogeographic Origin - Aniruddha Datta‐Roy; Matthew C. Brandley; Christopher C. Austin; Aaron M. Bauer; David James Harris; Salvador Carranza; Kanishka D. B. Ukuwela; Anslem De Silva; Krystal A. Tolley; K. Praveen Karanth; Maitreya Sil (Journal of Biogeography, 2025)
Aim We assess the systematic relationships and historical biogeographic patterns in the subfamily Scincinae, a group of lizards that primarily inhabits the Afro‐Madagascan and Saharo‐Arabian regions with isolated lineages in Europe, North America, East Asia, India and Sri Lanka. The contemporary distribution of these lineages on the historical Laurasian and Gondwanan landmasses make scincines an ideal system to study the roles of vicariance and dispersal on a geologic scale of tens of millions of years. Location Global. Taxon Subfamily Scincinae (Family Scincidae). Methods We conducted biogeographic analyses on a reconstructed, time‐calibrated species tree of scincine genera, including members of the other Scincidae subfamilies, using seven nuclear loci (~6 k base pairs). We also constructed a lineage‐through‐time plot to assess the timing of diversification within scincines. Results Our analysis estimated strong support for the monophyly of Scincinae that is further comprised a strongly‐supported Gondwanan clade nested within a broader Laurasian group. While most of the extant, genus‐level diversity within the Gondwanan clade was accrued post‐Eocene, the majority of the Laurasian lineages diverged during the Palaeocene or earlier, suggesting large‐scale extinctions on continents of Laurasian origin. Counterintuitively, scincines from India and Sri Lanka have distinct biogeographical origins despite a long tectonic association between these landmasses, suggesting at least two independent, long‐distance, trans‐oceanic dispersal events into the subcontinent. Our biogeographic analyses suggest that scincines likely originated in East and Southeast Asia during the late Cretaceous ( ca . 70 Ma), and eventually dispersed westwards to Africa and Madagascar, where their greatest current‐day species richness occurs. Main Conclusions Our study demonstrates the concomitant roles of dispersal and extinction in shaping modern‐day assemblages of ancient clades such as scincine lizards. Our range evolution analysis shows that despite the greater diversity observed in the Afro‐Madagascan region, the origin of scincines can be traced back to Southeast Asia and East Asia, followed by westward dispersals. These dispersals may have been followed by significant extinctions in tropical East Asia, resulting in relatively lower diversity of scincines in these regions. Notably, our analysis reveals that Sri Lankan and Peninsular Indian scincines have distinct evolutionary origins.

Correction: Predictive Modeling of Canadian Carbonatite-Hosted REE + / − Nb Deposits - Mohammad Parsa; Christopher J. M. Lawley; Renato Cumani; Ernst Schetselaar; Jeff Harris; David R. Lentz; Steven E. Zhang; Julie E. Bourdeau (Natural Resources Research, 2024)

Predictive Modeling of Canadian Carbonatite-Hosted REE +/− Nb Deposits - Mohammad Parsa; Christopher J. M. Lawley; Renato Cumani; Ernst Schetselaar; Jeff Harris; David R. Lentz; Steven E. Zhang; Julie E. Bourdeau (Natural Resources Research, 2024)
Carbonatites are the primary geological sources for rare earth elements (REEs) and niobium (Nb). This study applies machine learning techniques to generate national-scale prospectivity models and support mineral exploration targeting of Canadian carbonatite-hosted REE +/− Nb deposits. Extreme target feature label imbalance, diverse geological settings hosting these deposits throughout Canada, selecting negative labels, and issues regarding the interpretability of some machine learning models are major challenges impeding data-driven prospectivity modeling of carbonatite-hosted REE +/− Nb deposits. A multi-stage framework, exploiting global hierarchical tessellation model systems, data-space similarity measures, ensemble modeling, and Shapley additive explanations was coupled with convolutional neural networks (CNN) and random forest to meet the objectives of this work. A risk – return analysis was further implemented to assist with model interpretation and visualization. Multiple models were compared in terms of their predictive ability and their capability of reducing the search space for mineral exploration. The best-performing model, derived using a CNN that incorporates public geoscience datasets, exhibits an area under the curve for receiver operating characteristics plot of 0.96 for the testing labels, reducing the search area by 80%, while predicting all known carbonatite-hosted REE +/− Nb occurrences. The framework used in our study allows for an explicit definition of input vectors and provides a clear interpretation of outcomes generated by prospectivity models.

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Derivation of oral cancer slope factors for hexavalent chromium informed by pharmacokinetic models and in vivo genotoxicity data - Chad M. Thompson; Christopher Kirman; Mark A. Harris (Regulatory Toxicology and Pharmacology, 2023)

Wine quality assessment for Shiraz vertical vintages based on digital technologies and machine learning modeling. - Natalie Harris; Claudia Gonzalez Viejo; Christopher Barnes; Alexis Pang; Sigfredo Fuentes (Food Bioscience, 2023)

By the lakeshore: Multi-scalar geoarchaeology in the Turkana Basin at GaJj17, Koobi Fora (Kenya) - Kathryn L. Ranhorn; Silindokuhle S. Mavuso; Debra Colarossi; Tamara Dogandžić; Kaedan O'Brien; Mathilde Ribordy; Christopher Ssebuyungo; Shannon Warren; John W.K. Harris; David R. Braun; Emmanuel Ndiema (Quaternary Science Reviews, 2023)

The Ontology of Biological Attributes (OBA)—computational traits for the life sciences - Ray Stefancsik; James P. Balhoff; Meghan A. Balk; Robyn L. Ball; Susan M. Bello; Anita R. Caron; Elissa J. Chesler; Vinicius de Souza; Sarah Gehrke; Melissa Haendel; Laura W. Harris; Nomi L. Harris; et al. (Mammalian Genome, 2023)
Existing phenotype ontologies were originally developed to represent phenotypes that manifest as a character state in relation to a wild-type or other reference. However, these do not include the phenotypic trait or attribute categories required for the annotation of genome-wide association studies (GWAS), Quantitative Trait Loci (QTL) mappings or any population-focussed measurable trait data. The integration of trait and biological attribute information with an ever increasing body of chemical, environmental and biological data greatly facilitates computational analyses and it is also highly relevant to biomedical and clinical applications. The Ontology of Biological Attributes (OBA) is a formalised, species-independent collection of interoperable phenotypic trait categories that is intended to fulfil a data integration role. OBA is a standardised representational framework for observable attributes that are characteristics of biological entities, organisms, or parts of organisms. OBA has a modular design which provides several benefits for users and data integrators, including an automated and meaningful classification of trait terms computed on the basis of logical inferences drawn from domain-specific ontologies for cells, anatomical and other relevant entities. The logical axioms in OBA also provide a previously missing bridge that can computationally link Mendelian phenotypes with GWAS and quantitative traits. The term components in OBA provide semantic links and enable knowledge and data integration across specialised research community boundaries, thereby breaking silos.

Pollinator spillover: Hay cutting of grass with white clover, Trifolium repens, displaces bees and increases their abundance in adjacent patches of bramble, Rubus fruticosus - Ciaran Harris; Rosy Christopher; Seshi Humphrey-Ackumey; Rachel Mercer; Phoebe Ney; Francis L.W. Ratnieks (Agriculture, Ecosystems & Environment, 2023)

A facies- and sequence stratigraphy-based reservoir model for a carbonate reef complex: South Swan Hills oil pool, Alberta - Christopher V. Noyahr; John A.W. Weissenberger; Nicholas B. Harris; Jonathan Banks (Marine and Petroleum Geology, 2023)

Mid-Holocene intensification of Southern Hemisphere westerly winds and implications for regional climate dynamics - Jamie Tamhane; Zoë A. Thomas; Haidee Cadd; Matthew R.P. Harris; Chris Turney; Christopher E. Marjo; Huixin Wang; Rabeya Akter; Panayiotis Panaretos; Amalia Halim; Patricia S. Gadd; Stefanie Carter; et al. (Quaternary Science Reviews, 2023)

Using the Flocculation Index to optimise coagulant dosing during drinking water treatment - Mahmoud Khedher; John Awad; Erica Donner; Barbara Drigo; Rolando Fabris; Martin Harris; Kalan Braun; Christopher W.K. Chow (Journal of Water Process Engineering, 2023)

Coral rubble dynamics in the Anthropocene and implications for reef recovery - Tania M. Kenyon; Christopher Doropoulos; Kennedy Wolfe; Gregory E. Webb; Sophie Dove; Daniel Harris; Peter J. Mumby (Limnology and Oceanography, 2023)
With rubble predicted to increase on coral reefs worldwide, we review the physical, biological, and ecological dynamics of rubble beds, with a focus on how rubble generation, mobilization, binding, and coral recruitment is expected to change on future reefs. Major disturbances, including storms and coral bleaching, are predicted to increase in intensity and frequency, and—like localized impacts including blast fishing and ship groundings—generate large quantities of coral rubble. Reefs will have increasingly smaller recovery windows between successive disturbances, leading to persistence of unstable rubble beds on reefs. With more severe storms and increased bioerosion on future reefs, rubble mobilization thresholds will be met more often as smaller, less complex rubble pieces are generated. If rubble remains stable for adequate time, it can be bound by organisms including sponges and coralline algae, and eventually be cemented. However, increasing rubble mobilization frequencies will reduce the time available for binding, while changing ocean chemistry could reduce the efficacy of calcifying binders. Ultimately, increased rubble cover will negatively impact coral recruitment into rubble beds. Rubble mobilization abrades and smothers corals, and rubble beds typically experience altered environmental and ecological conditions to the coral frameworks that precede them. Several knowledge gaps exist in relation to improved rubble mobilization thresholds, binding rates and strengths, and coral survival in varying rubble bed types and hydrodynamic regimes. Addressing these knowledge gaps will improve our ability to predict the recovery trajectory of rubble beds and assess the need for stabilization interventions.

Cover Image - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)

Exogenous polyunsaturated fatty acids ( PUFAs ) influence permeability, antimicrobial peptide resistance, biofilm formation and membrane phospholipid structure in an A‐layer and non‐A ‐layer strain of Aeromonas salmonicida - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)
Aeromonas salmonicida is a Gram‐negative bacterium that can infect a wide host range of fish populations, including salmonids and non‐salmonids as well as freshwater and marine life. Some strains of A. salmonicida cause the disease furunculosis, which can cause lethargy, intestinal inflammation, ulcers, haemorrhaging and death. The infection is spread through fish‐to‐fish contact, and the presence of infection can have devastating effects on cultivated fish populations. The purpose of this study was to explore the ability of non‐A‐layer and A‐layer A. salmonicida strains to incorporate polyunsaturated fatty acids (PUFAs) into their lipid profile and test the phenotypic effects thereof. Lipids were extracted from PUFA‐exposed cultures and analysed for lipid modification by thin‐layer chromatography and ultraperformance liquid chromatography‐mass spectrometry, showing A. salmonicida , regardless of A‐layer, capable of incorporating all seven of the PUFAs studied. Phenotypic effects were determined through the use of assays that tested for biofilm formation, membrane permeability and cyclic peptide susceptibility. Temperature‐dependent effects on biofilm formation were observed, and PUFA exposure showed significant ( p

Hybrid Lattice-Boltzmann-Potential Flow Simulations of Turbulent Flow around Submerged Structures - Christopher M. O’Reilly; Stephan T. Grilli; Christian F. Janßen; Jason M. Dahl; Jeffrey C. Harris (Journal of Marine Science and Engineering, 2022)
We report on the development and validation of a 3D hybrid Lattice Boltzmann Model (LBM), with Large Eddy Simulation (LES), to simulate the interactions of incompressible turbulent flows with ocean structures. The LBM is based on a perturbation method, in which the velocity and pressure are expressed as the sum of an inviscid flow and a viscous perturbation. The far- to near-field flow is assumed to be inviscid and represented by potential flow theory, which can be efficiently modeled with a Boundary Element Method (BEM). The near-field perturbation flow around structures is modeled by the Navier–Stokes (NS) equations, based on a Lattice Boltzmann Method (LBM) with a Large Eddy Simulation (LES) of the turbulence. In the paper, we present the hybrid model formulation, in which a modified LBM collision operator is introduced to simulate the viscous perturbation flow, resulting in a novel perturbation LBM (pLBM) approach. The pLBM is then extended for the simulation of turbulence using the LES and a wall model to represent the viscous/turbulent sub-layer near solid boundaries. The hybrid model is first validated by simulating turbulent flows over a flat plate, for moderate to large Reynolds number values, Re ∈[3.7×104;1.2×106]; the plate friction coefficient and near-field turbulence properties computed with the model are found to agree well with both experiments and direct NS simulations. We then simulate the flow past a NACA-0012 foil using a regular LBM-LES and the new hybrid pLBM-LES models with the wall model, for Re = 1.44×106. A good agreement is found for the computed lift and drag forces, and pressure distribution on the foil, with experiments and results of other numerical methods. Results obtained with the pLBM model are either nearly identical or slightly improved, relative to those of the standard LBM, but are obtained in a significantly smaller computational domain and hence at a much reduced computational cost, thus demonstrating the benefits of the new hybrid approach.

The Watts Connectedness Scale: a new scale for measuring a sense of connectedness to self, others, and world - Rosalind Watts; Hannes Kettner; Dana Geerts; Sam Gandy; Laura Kartner; Lea Mertens; Christopher Timmermann; Matthew M. Nour; Mendel Kaelen; David Nutt; Robin Carhart-Harris; Leor Roseman (Psychopharmacology, 2022)
Rationale A general feeling of disconnection has been associated with mental and emotional suffering. Improvements to a sense of connectedness to self, others and the wider world have been reported by participants in clinical trials of psychedelic therapy. Such accounts have led us to a definition of the psychological construct of ‘connectedness’ as ‘a state of feeling connected to self, others and the wider world’. Existing tools for measuring connectedness have focused on particular aspects of connectedness, such as ‘social connectedness’ or ‘nature connectedness’, which we hypothesise to be different expressions of a common factor of connectedness. Here, we sought to develop a new scale to measure connectedness as a construct with these multiple domains. We hypothesised that (1) our scale would measure three separable subscale factors pertaining to a felt connection to ‘self’, ‘others’ and ‘world’ and (2) improvements in total and subscale WCS scores would correlate with improved mental health outcomes post psychedelic use. Objectives To validate and test the ‘Watts Connectedness Scale’ (WCS). Methods Psychometric validation of the WCS was carried out using data from three independent studies. Firstly, we pooled data from two prospective observational online survey studies. The WCS was completed before and after a planned psychedelic experience. The total sample of completers from the online surveys was N = 1226. Exploratory and confirmatory factor analysis were performed, and construct and criterion validity were tested. A third dataset was derived from a double-blind randomised controlled trial (RCT) comparing psilocybin-assisted therapy ( n = 27) with 6 weeks of daily escitalopram ( n = 25) for major depressive disorder (MDD), where the WCS was completed at baseline and at a 6-week primary endpoint. Results As hypothesised, factor analysis of all WCS items revealed three main factors with good internal consistency. WCS showed good construct validity. Significant post-psychedelic increases were observed for total connectedness scores (η2 = 0.339, p < 0.0001), as well as on each of its subscales ( p < 0.0001). Acute measures of ‘mystical experience’, ‘emotional breakthrough’, and ‘communitas’ correlated positively with post-psychedelic changes in connectedness ( r = 0.42, r = 0.38, r = 0.42, respectively, p < 0.0001). In the RCT, psilocybin therapy was associated with greater increases in WCS scores compared with the escitalopram arm ( η p 2 = 0.133, p = 0.009). Conclusions The WCS is a new 3-dimensional index of felt connectedness that may sensitively measure therapeutically relevant psychological changes post-psychedelic use. We believe that the operational definition of connectedness captured by the WCS may have broad relevance in mental health research.

Mixed-Mode Fracture Modelling of the Near-Wellbore Interaction Between Hydraulic Fracture and Natural Fracture - Xun Xi; Zoe K. Shipton; Jackie E. Kendrick; Andrew Fraser‑Harris; Julien Mouli-Castillo; Katriona Edlmann; Christopher I. McDermott; Shangtong Yang (Rock Mechanics and Rock Engineering, 2022)
The interaction between hydraulic fractures (HF) and natural fractures (NF) is one of the most fundamental phenomena in hydraulic fracturing. The near-wellbore interaction between HF and NF significantly affects fracking-related operations including the injected fluid flow, proppant transport and well productivity. However, the nature of fracturing modes, combined with hydro-mechanical coupling, poses great difficulties and challenges in addressing this problem. Literature review suggests that little research has been undertaken on near-wellbore interaction, especially considering the fully coupled hydro-mechanical mixed-mode fracturing process. This paper develops a new fracture model incorporating the Mohr–Coulomb criterion with the cohesive crack model. The model is implemented into ABAQUS solver by in-house FORTRAN subroutines. The rock matrix and cohesive crack interfaces are both coupled with fluid flow. The developed model is then validated by comparing the results with analytical solutions and experimental results. Moreover, the effects of approach angle, NF location, in situ stress, cohesion strength and friction angle of NF, and flow rate on the near-wellbore interaction are investigated. Three interaction modes, i.e., cross, deflect and offset, are reproduced through the numerical method. The crack deflection into NF is a shear-dominated mixed-mode fracture. A high injection pressure in the wellbore tends to drive the HF to cross a NF located close to the wellbore. The smaller the cohesion strength and friction angle of NF is, the larger the offsetting ratio is. A low injection flow rate can help activate natural fractures near the wellbore when intersected by HF.

Population genetics reveals bidirectional fish movement across the Continental Divide via an interbasin water transfer - Audrey C. Harris; Sara J. Oyler-McCance; Jennifer A. Fike; Matthew P. Fairchild; Christopher M. Kennedy; Harry J. Crockett; Dana L. Winkelman; Yoichiro Kanno (Conservation Genetics, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effects of artificial light at night on fishes: A synthesis with future research priorities - Arshpreet Bassi; Oliver P. Love; Steven J. Cooke; Theresa R. Warriner; Christopher M. Harris; Christine L. Madliger (Fish and Fisheries, 2022)
Nearly all organisms rely on natural fluctuations of light as cues for synchronizing physiological processes and behavioural actions associated with foraging, growth, sleep and rest, reproduction, and migration. Consequently, although artificial lighting sources have provided a plethora of benefits for humans, they can lead to disruptions for wild organisms. With one quarter of the human population living within 100 km of coastlines, there is great potential for artificial light at night (ALAN) to influence the physiology, behaviour and fitness of fishes. Through a review of the literature ( n = 584 publications focused on the effects of ALAN on individual organisms or ecosystems), we illustrate that most papers have concentrated on terrestrial species (59%) compared with aquatic species (20%) or a mixed approach (21%). Fishes have been underrepresented in comparison with many other taxa such as birds, insects and mammals, representing the focus of less than 8% of taxa‐specific publications. While the number of publications per year focusing on fishes has generally been increasing since the mid‐2000s, there has been a downturn in publication rate in the last few years. To understand where research related to ALAN in fishes has been focused, we partitioned studies into categories and found that publications have mostly concerned behaviour (41.0%), abundance and community structure (24.4%), and physiology (22.8%), while the longer‐term effects on fitness (6.9%) are lacking. We synthesize the research completed in fishes and outline future priorities that will help ascertain the short‐ and long‐term consequences of this relatively novel stressor for fish health and persistence.

Drought at a coastal wetland affects refuelling and migration strategies of shorebirds - Alexandra M. Anderson; Christian Friis; Cheri L. Gratto-Trevor; Christopher M. Harris; Oliver P. Love; R. I. Guy Morrison; Sean W. J. Prosser; Erica Nol; Paul A. Smith (Oecologia, 2021)
Droughts can affect invertebrate communities in wetlands, which can have bottom-up effects on the condition and survival of top predators. Shorebirds, key predators at coastal wetlands, have experienced widespread population declines and could be negatively affected by droughts. We explored, in detail, the effects of drought on multiple aspects of shorebird stopover and migration ecology by contrasting a year with average wet/dry conditions (2016) with a year with moderate drought (2017) at a major subarctic stopover site on southbound migration. We also examined the effects of drought on shorebird body mass during stopover across 14 years (historical: 1974–1982 and present-day: 2014–2018). For the detailed comparison of two years, in the year with moderate drought we documented lower invertebrate abundance at some sites, higher prey family richness in shorebird faecal samples, lower shorebird refuelling rates, shorter stopover durations for juveniles, and, for most species, a higher probability of making a subsequent stopover in North America after departing the subarctic, compared to the year with average wet/dry conditions. In the 14-year dataset, shorebird body mass tended to be lower in drier years. We show that even short-term, moderate drought conditions can negatively affect shorebird refuelling performance at coastal wetlands, which may carry-over to affect subsequent stopover decisions. Given shorebird population declines and predicted changes in the severity and duration of droughts with climate change, researchers should prioritize a better understanding of how droughts affect shorebird refuelling performance and survival.

Interactive effects of sediments and urchins on the composition and structure of tropical macroalgal assemblages - Rosalie J. Harris; Shaun K. Wilson; Christopher J. Fulton (Marine Biology, 2021)

Modelling Rock Fracture Induced By Hydraulic Pulses - Xun Xi; Shangtong Yang; Christopher I. McDermott; Zoe K. Shipton; Andrew Fraser-Harris; Katriona Edlmann (Rock Mechanics and Rock Engineering, 2021)
Soft cyclic hydraulic fracturing has become an effective technology used in subsurface energy extraction which utilises cyclic hydraulic flow pressure to fracture rock. This new technique induces fatigue of rock to reduce the breakdown pressure and potentially the associated risk of seismicity. To control the fracturing process and achieve desirable fracture networks for enhanced permeability, the rock response under cyclic hydraulic stimulation needs to be understood. However, the mechanism for cyclic stimulation-induced fatigue of rock is rather unclear and to date there is no implementation of fatigue degradation in modelling the rock response under hydraulic cyclic loading. This makes accurate prediction of rock fracture under cyclic hydraulic pressure impossible. This paper develops a numerical method to model rock fracture induced by hydraulic pulses with consideration of rock fatigue. The fatigue degradation is based on S–N curves ( S for cyclic stress and N for cycles to failure) and implemented into the constitutive relationship for fracture of rock using in-house FORTRAN scripts and ABAQUS solver. The cohesive crack model is used to simulate discrete crack propagation in the rock which is coupled with hydraulic flow and pore pressure capability. The developed numerical model is validated via experimental results of pulsating hydraulic fracturing of the rock. The effects of flow rate and frequency of cyclic injection on borehole pressure development are investigated. A new loading strategy for pulsating hydraulic fracturing is proposed. It has been found that hydraulic pulses can reduce the breakdown pressure of rock by 10–18% upon 10–4000 cycles. Using the new loading strategy, a slow and steady rock fracture process is obtained while the failure pressure is reduced.

Disturbance type and species life history predict mammal responses to humans - Justin P. Suraci; Kaitlyn M. Gaynor; Maximilian L. Allen; Peter Alexander; Justin S. Brashares; Sara Cendejas‐Zarelli; Kevin Crooks; L. Mark Elbroch; Tavis Forrester; Austin M. Green; Jeffrey Haight; Nyeema C. Harris; et al. (Global Change Biology, 2021)
Human activity and land use change impact every landscape on Earth, driving declines in many animal species while benefiting others. Species ecological and life history traits may predict success in human‐dominated landscapes such that only species with “winning” combinations of traits will persist in disturbed environments. However, this link between species traits and successful coexistence with humans remains obscured by the complexity of anthropogenic disturbances and variability among study systems. We compiled detection data for 24 mammal species from 61 populations across North America to quantify the effects of (1) the direct presence of people and (2) the human footprint (landscape modification) on mammal occurrence and activity levels. Thirty‐three percent of mammal species exhibited a net negative response (i.e., reduced occurrence or activity) to increasing human presence and/or footprint across populations, whereas 58% of species were positively associated with increasing disturbance. However, apparent benefits of human presence and footprint tended to decrease or disappear at higher disturbance levels, indicative of thresholds in mammal species’ capacity to tolerate disturbance or exploit human‐dominated landscapes. Species ecological and life history traits were strong predictors of their responses to human footprint, with increasing footprint favoring smaller, less carnivorous, faster‐reproducing species. The positive and negative effects of human presence were distributed more randomly with respect to species trait values, with apparent winners and losers across a range of body sizes and dietary guilds. Differential responses by some species to human presence and human footprint highlight the importance of considering these two forms of human disturbance separately when estimating anthropogenic impacts on wildlife. Our approach provides insights into the complex mechanisms through which human activities shape mammal communities globally, revealing the drivers of the loss of larger predators in human‐modified landscapes.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Using Ship-Deployed High-Endurance Unmanned Aerial Vehicles for the Study of Ocean Surface and Atmospheric Boundary Layer Processes - Christopher J. Zappa; Scott M. Brown; Nathan J. M. Laxague; Tejendra Dhakal; Ryan A. Harris; Aaron M. Farber; Ajit Subramaniam (Frontiers in Marine Science, 2020)

Discovery of cryptotephra at Middle–Upper Paleolithic sites Arma Veirana and Riparo Bombrini, Italy: a new link for broader geographic correlations - Jayde N. Hirniak; Eugene I. Smith; Racheal Johnsen; Minghua Ren; Jamie Hodgkins; Caley Orr; Fabio Negrino; Julien Riel‐Salvatore; Shelby Fitch; Christopher E. Miller; Andrea Zerboni; Guido S. Mariani; et al. (Journal of Quaternary Science, 2020)
Chemical characterization of cryptotephra is critical for temporally linking archaeological sites. Here, we describe cryptotephra investigations of two Middle–Upper Paleolithic sites from north‐west Italy, Arma Veirana and Riparo Bombrini. Cryptotephra are present as small ( 75 wt.%) with low FeO ( 2 O/Na 2 O > 1 and P2 is also a high silica rhyolite (>75 wt.%) but with higher FeO (2.33–2.65 wt.%). Shards at Riparo Bombrini (P3) are of the same composition as P1 shards at Arma Veirana, providing a distinct link between deposits at both sites. Geochemical characteristics suggest three possible sources for P1 and P3: eruptions from Lipari Island (56–37.7 ka) in Italy, the Acigöl volcanic field (200–20 ka) in Turkey and the Miocene Kirka‐Phrigian caldera (18 Ma) in Turkey. Eruptions from Lipari Island are the most likely source for P1,3 cryptotephra. This study highlights how cryptotephra can benefit archaeology, by providing a direct link between Arma Veirana and Riparo Bombrini as well as other deposits throughout the Mediterranean.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Tidal Variation in Cohesive Sediment Distribution and Sensitivity to Flocculation and Bed Consolidation in An Idealized, Partially Mixed Estuary - Danielle R.N. Tarpley; Courtney K. Harris; Carl T. Friedrichs; Christopher R. Sherwood (Journal of Marine Science and Engineering, 2019)
Particle settling velocity and erodibility are key factors that govern the transport of sediment through coastal environments including estuaries. These are difficult to parameterize in models that represent mud, whose properties can change in response to many factors, including tidally varying suspended sediment concentration (SSC) and shear stress. Using the COAWST (Coupled Ocean-Atmosphere-Wave-Sediment Transport) model framework, we implemented bed consolidation, sediment-induced stratification, and flocculation formulations within an idealized two-dimensional domain that represented the longitudinal dimension of a micro-tidal, muddy, partially mixed estuary. Within the Estuarine Turbidity Maximum (ETM), SSC and median floc diameter varied by a factor of four over the tidal cycle. Downstream of the ETM, the median floc size and SSC were several times smaller and showed less tidal variation (~20% or less). The suspended floc distributions only reached an equilibrium size as a function of SSC and shear in the ETM at peak tidal flow. In general, flocculation increased particle size, which reduced SSC by half in the ETM through increased settling velocity. Consolidation also limited SSC by reduced resuspension, which then limited floc growth through reduced SSC by half outside of the ETM. Sediment-induced stratification had negligible effects in the parameter space examined. Efforts to lessen the computation cost of the flocculation routine by reducing the number of size classes proved difficult; floc size distribution and SSC were sensitive to specification of size classes by factors of 60% and 300%, respectively.

Synergies in Operational Oceanography: The Intrinsic Need for Sustained Ocean Observations - Fraser Davidson; Aida Alvera-Azcárate; Alexander Barth; Gary B. Brassington; Eric P. Chassignet; Emanuela Clementi; Pierre De Mey-Frémaux; Prasanth Divakaran; Christopher Harris; Fabrice Hernandez; Patrick Hogan; Lars R. Hole; et al. (Frontiers in Marine Science, 2019)

Sediment Transport Model Including Short-Lived Radioisotopes: Model Description and Idealized Test Cases - Justin J. Birchler; Courtney K. Harris; Christopher R. Sherwood; Tara A. Kniskern (Journal of Marine Science and Engineering, 2018)
Geochronologies derived from sediment cores in coastal locations are often used to infer event bed characteristics such as deposit thicknesses and accumulation rates. Such studies commonly use naturally occurring, short-lived radioisotopes, such as Beryllium-7 (7Be) and Thorium-234 (234Th), to study depositional and post-depositional processes. These radioisotope activities, however, are not generally represented in sediment transport models that characterize coastal flood and storm deposition with grain size patterns and deposit thicknesses. We modified the Community Sediment Transport Modeling System (CSTMS) to account for reactive tracers and used this capability to represent the behavior of these short-lived radioisotopes on the sediment bed. This paper describes the model and presents results from a set of idealized, one-dimensional (vertical) test cases. The model configuration represented fluvial deposition followed by periods of episodic storm resuspension. Sensitivity tests explored the influence on seabed radioisotope profiles by the intensities of bioturbation and wave resuspension and the thickness of fluvial deposits. The intensity of biodiffusion affected the persistence of fluvial event beds as evidenced by 7Be. Both resuspension and biodiffusion increased the modeled seabed inventory of 234Th. A thick fluvial deposit increased the seabed inventory of 7Be and 234Th but mixing over time greatly reduced the difference in inventory of 234Th in fluvial deposits of different thicknesses.

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Southern Hemisphere westerly wind influence on southern New Zealand hydrology during the Lateglacial and Holocene - Harris J. Anderson; Christopher M. Moy; Marcus J. Vandergoes; Jonathan E. Nichols; Christina R. Riesselman; Robert Van Hale (Journal of Quaternary Science, 2018)
The strength and latitudinal position of the southern westerly winds (SWW) influence mid‐latitude precipitation and carbon cycling in the Southern Ocean. Despite the important role the westerlies play in the global climate system, past variability is poorly constrained. Here, we present a geochemical record of hydroclimate change from Lake Von in south‐west New Zealand that spans the last 16 000 years. During the Lateglacial and early Holocene, we find stratigraphic and geochemical evidence for three distinct periods of low lake levels that occur during North Atlantic cold events when the Intertropical Convergence Zone is displaced southwards, Southern Ocean upwelling is enhanced and the Antarctic is rapidly warming. We attribute these hydrological changes to southward shifts of the SWW and associated storm tracks that cause arid conditions in southern New Zealand. During the early Holocene, we find evidence for an extended period of low lake levels that are caused by a combination of diminished wind strength, higher air temperatures and reduced seasonality. Finally, we interpret an overall intensification of the SWW after 5500 cal a bp. Our results support the idea that climate mechanisms originating in the high latitudes and the tropics work together to influence the SWW on millennial timescales.

Correction to: The hidden therapist: evidence for a central role of music in psychedelic therapy - Mendel Kaelen; Bruna Giribaldi; Jordan Raine; Lisa Evans; Christopher Timmermann; Natalie Rodriguez; Leor Roseman; Amanda Feilding; David Nutt; Robin Carhart-Harris (Psychopharmacology, 2018)

The hidden therapist: evidence for a central role of music in psychedelic therapy - Mendel Kaelen; Bruna Giribaldi; Jordan Raine; Lisa Evans; Christopher Timmerman; Natalie Rodriguez; Leor Roseman; Amanda Feilding; David Nutt; Robin Carhart-Harris (Psychopharmacology, 2018)

Effects of acute resistance training modality on corticospinal excitability, intra-cortical and neuromuscular responses - Christopher Latella; Wei-Peng Teo; Dale Harris; Brendan Major; Dan VanderWesthuizen; Ashlee M. Hendy (European Journal of Applied Physiology, 2017)

An evaluation of feather corticosterone as a biomarker of fitness and an ecologically relevant stressor during breeding in the wild - Christopher M. Harris; Christine L. Madliger; Oliver P. Love (Oecologia, 2017)

Genome‐wide association of functional traits linked with C ampylobacter jejuni survival from farm to fork - Koji Yahara; Guillaume Méric; Aidan J. Taylor; Stefan P. W. de Vries; Susan Murray; Ben Pascoe; Leonardos Mageiros; Alicia Torralbo; Ana Vidal; Anne Ridley; Sho Komukai; Helen Wimalarathna; et al. (Environmental Microbiology, 2017)
Summary Campylobacter jejuni is a major cause of bacterial gastroenteritis worldwide, primarily associated with the consumption of contaminated poultry. C. jejuni lineages vary in host range and prevalence in human infection, suggesting differences in survival throughout the poultry processing chain. From 7343 MLST‐characterised isolates, we sequenced 600 C. jejuni and C. coli isolates from various stages of poultry processing and clinical cases. A genome‐wide association study (GWAS) in C. jejuni ST‐21 and ST‐45 complexes identified genetic elements over‐represented in clinical isolates that increased in frequency throughout the poultry processing chain. Disease‐associated SNPs were distinct in these complexes, sometimes organised in haplotype blocks. The function of genes containing associated elements was investigated, demonstrating roles for cj1377c in formate metabolism, nuoK in aerobic survival and oxidative respiration, and cj1368‐70 in nucleotide salvage. This work demonstrates the utility of GWAS for investigating transmission in natural zoonotic pathogen populations and provides evidence that major C. jejuni lineages have distinct genotypes associated with survival, within the host specific niche, from farm to fork.

Paradigms for parasite conservation - Eric R. Dougherty; Colin J. Carlson; Veronica M. Bueno; Kevin R. Burgio; Carrie A. Cizauskas; Christopher F. Clements; Dana P. Seidel; Nyeema C. Harris (Conservation Biology, 2016)
Parasitic species, which depend directly on host species for their survival, represent a major regulatory force in ecosystems and a significant component of Earth's biodiversity. Yet the negative impacts of parasites observed at the host level have motivated a conservation paradigm of eradication, moving us farther from attainment of taxonomically unbiased conservation goals. Despite a growing body of literature highlighting the importance of parasite‐inclusive conservation, most parasite species remain understudied, underfunded, and underappreciated. We argue the protection of parasitic biodiversity requires a paradigm shift in the perception and valuation of their role as consumer species, similar to that of apex predators in the mid‐20th century. Beyond recognizing parasites as vital trophic regulators, existing tools available to conservation practitioners should explicitly account for the unique threats facing dependent species. We built upon concepts from epidemiology and economics (e.g., host‐density threshold and cost‐benefit analysis) to devise novel metrics of margin of error and minimum investment for parasite conservation. We define margin of error as the risk of accidental host extinction from misestimating equilibrium population sizes and predicted oscillations, while minimum investment represents the cost associated with conserving the additional hosts required to maintain viable parasite populations. This framework will aid in the identification of readily conserved parasites that present minimal health risks. To establish parasite conservation, we propose an extension of population viability analysis for host–parasite assemblages to assess extinction risk. In the direst cases, ex situ breeding programs for parasites should be evaluated to maximize success without undermining host protection. Though parasitic species pose a considerable conservation challenge, adaptations to conservation tools will help protect parasite biodiversity in the face of an uncertain environmental future.

Particle Filters to Estimate Properties of Confined Aquifers - Graeme Field; German Tavrisov; Christopher Brown; Alan Harris; O. Patrick Kreidl (Water Resources Management, 2016)

Modeling of SMF tsunami hazard along the upper US East Coast: detailed impact around Ocean City, MD - Stephan T. Grilli; Christopher O’Reilly; Jeffrey C. Harris; Tayebeh Tajalli Bakhsh; Babak Tehranirad; Saeideh Banihashemi; James T. Kirby; Christopher D. P. Baxter; Tamara Eggeling; Gangfeng Ma; Fengyan Shi (Natural Hazards, 2015)

Development of nuclear microsatellite markers for American badger subspecies (Taxidea taxus spp.) using next generation sequencing - Yessica Rico; David Paetkau; Leanne R. Harris; Josh Sayers; Danielle Ethier; Christopher J. Kyle (Conservation Genetics Resources, 2014)

Model Behavior and Sensitivity in an Application of the Cohesive Bed Component of the Community Sediment Transport Modeling System for the York River Estuary, VA, USA - Kelsey Fall; Courtney Harris; Carl Friedrichs; J. Rinehimer; Christopher Sherwood (Journal of Marine Science and Engineering, 2014)
The Community Sediment Transport Modeling System (CSTMS) cohesive bed sub-model that accounts for erosion, deposition, consolidation, and swelling was implemented in a three-dimensional domain to represent the York River estuary, Virginia. The objectives of this paper are to (1) describe the application of the three-dimensional hydrodynamic York Cohesive Bed Model, (2) compare calculations to observations, and (3) investigate sensitivities of the cohesive bed sub-model to user-defined parameters. Model results for summer 2007 showed good agreement with tidal-phase averaged estimates of sediment concentration, bed stress, and current velocity derived from Acoustic Doppler Velocimeter (ADV) field measurements. An important step in implementing the cohesive bed model was specification of both the initial and equilibrium critical shear stress profiles, in addition to choosing other parameters like the consolidation and swelling timescales. This model promises to be a useful tool for investigating the fundamental controls on bed erodibility and settling velocity in the York River, a classical muddy estuary, provided that appropriate data exists to inform the choice of model parameters.

Three-dimensional Quantification of Femoral Head Shape in Controls and Patients with Cam-type Femoroacetabular Impingement - Michael D. Harris; Shawn P. Reese; Christopher L. Peters; Jeffrey A. Weiss; Andrew E. Anderson (Annals of Biomedical Engineering, 2013)

The distribution of quick phase interval durations in human optokinetic nystagmus - Jonathan Waddington; Christopher M. Harris (Experimental Brain Research, 2013)

ENU mutagenesis in mice identifies candidate genes for hypogonadism - Jeffrey Weiss; Lisa A. Hurley; Rebecca M. Harris; Courtney Finlayson; Minghan Tong; Lisa A. Fisher; Jennifer L. Moran; David R. Beier; Christopher Mason; J. Larry Jameson (Mammalian Genome, 2012)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 1. Overview and Problem Formulation - Donald D. MacDonald; Dwayne R. J. Moore; Christopher G. Ingersoll; Dawn E. Smorong; R. Scott Carr; Ron Gouguet; David Charters; Duane Wilson; Tom Harris; Jon Rauscher; Susan Roddy; John Meyer (Archives of Environmental Contamination and Toxicology, 2011)

Germline PKHD1 mutations are protective against colorectal cancer - Christopher J. Ward; Yanhong Wu; Ruth A. Johnson; John R. Woollard; Eric J. Bergstralh; Mine S. Cicek; Jason Bakeberg; Sandro Rossetti; Christina M. Heyer; Gloria M. Petersen; Noralene M. Lindor; Stephen N. Thibodeau; et al. (Human Genetics, 2011)

Patterns of mussel recruitment in southern Africa: a caution about using artificial substrata to approximate natural recruitment - Kathleen E. Reaugh-Flower; George M. Branch; Jean M. Harris; Christopher D. McQuaid; Bronwen Currie; Arthur Dye; Bruce Robertson (Marine Biology, 2010)

Remote Detection of Marine Microbes, Small Invertebrates, Harmful Algae, and Biotoxins using the Environmental Sample Processor (ESP) - Christopher Scholin; Gregory Doucette; Scott Jensen; Brent Roman; Douglas Pargett; Roman Marin III; Christina Preston; William Jones; Jason Feldman; Cheri Everlove; Adeline Harris; Nilo Alvarado; et al. (Oceanography, 2009)

Construction dynamics of a lava channel - Andrew J. L. Harris; Massimiliano Favalli; Francesco Mazzarini; Christopher W. Hamilton (Bulletin of Volcanology, 2009)

The Main Sequence of Saccades Optimizes Speed-accuracy Trade-off - Christopher M. Harris; Daniel M. Wolpert (Biological Cybernetics, 2006)

Sediment Dynamics in the Adriatic Sea Investigated with Coupled Models - Christopher Sherwood; Jeffrey Book; Sandro Carniel; Luigi Cavaleri; Jacopo Chiggiato; Himangshu Das; James Doyle; Courtney Harris; Alan Niedoroda; Henry Perkins; Pierre-Marie Poulain; Julie Pullen; et al. (Oceanography, 2004)

The research potential of tissue from a cadaveric donor - Christopher Womack; Neil M. Gray; Lesley J. Howes; Michael D. Harris (Cell and Tissue Banking, 2002)

Rapid in vivo functional analysis of transgenes in mice using whole body imaging of luciferase expression - Weisheng Zhang; Jian Q. Feng; Stephen E. Harris; Pamela R. Contag; David K. Stevenson; Christopher H. Contag (Transgenic Research, 2001)

Variation in isomeric products of a phosphodiesterase from the chloroplasts of Phaseolus vulgaris in response to cations - Penny E. Diffley; Alan Geisbrecht; Russell P. Newton; Michael Oliver; Christopher J. Smith; Judith Vaughan; Jan van Cleef; Jan van Geyschem; Terence J. Walton; Mark Bayliss; A. Gareth Brenton; Frank M. Harris; et al. (Plant Biosystems, 2001)

Ionizing radiation stimulates octamer factor DNA binding activity in human carcinoma cells - Rachel L. Meighan-Mantha; Anna T. Riegel; Simeng Suy; Violaine Harris; Fuh-Han Wang; Christopher Lozano; Theresa L. Whiteside; Usha Kasid (Molecular and Cellular Biochemistry, 1999)

Lead transport in IEC-6 intestinal epithelial cells - Christopher M. Dekaney; Edward D. Harris; Gerald R. Bratton; Laurie A. Jaeger (Biological Trace Element Research, 1997)

Detection and quantification of Pseudo‐nitzschia australis in cultured and natural populations using LSU rRNA‐targeted probes - Christopher Scholin; Peter Miller; Kurt Buck; Francisco Chavez; Paul Harris; Paul Haydock; Judith Howard; Gerard Cangelosi (Limnology and Oceanography, 1997)
Pseudo‐nitzschia australis Frenguelli is a marine pennate diatom associated with the production of domoic acid— a neuroexcitatory amino acid linked to illness and mortality of humans and wildlife. Distinguishing P. australis from its co‐occurring congeners is labor intensive and time consuming because of a requirement for scanning electron microscopy. Here, we apply large‐subunit ribosomal RNA (LSU rRNA)‐targeted oligonucleotides in whole‐cell and sandwich hybridization formats to identify and enumerate this species collected from pure cultures and natural populations. Whole‐cell hybridization employed fluorescently labeled probes, filter‐based sample processing, and epifluorescence microscopy to enumerate labeled cells. In contrast, sandwich hybridization was accomplished by homogenizing cells in a chaotropic solution and performing two hybridization reactions: capture of LSU rRNA using an oligonucieotide coupled to a macroscopic solid support and binding of signal probe to a region of LSU rRNA near that of the capture site. Sandwich hybrids were detected colorimetrically; color intensity was proportional to the abundance of target species in the original sample. The sandwich hybridization assay was semiautomated with a robotic processor. Both whole‐cell and sandwich hybridization are useful techniques for identifying P. australis as it occurs in nature. Sandwich hybridization potentially offers the most rapid and simple means to accomplish this task when screening large numbers of environmental samples.

Isozyme variation inFaidherbia albida (Leguminosae, Mimosoideae) - Stephen A. Harris; Christopher W. Fagg; Richard D. Barnes (Plant Systematics and Evolution, 1997)

The ethology of saccades: a non-cognitive model - Christopher M. Harris (Biological Cybernetics, 1989)